2011
DOI: 10.1016/j.chemosphere.2011.09.045
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and seasonal variability of trace elements in atmospheric particulate in the Venice Lagoon

Abstract: a b s t r a c tSize distribution and selected element concentrations of atmospheric particulate matter (PM) were investigated in the Venice Lagoon, at three sites characterised by different anthropogenic influence. The PM 10 samples were collected in six size fractions (10-7.2, 7.2-3.0, 3.0-1.5, 1.5-0.95; 0.95-0.49 and <0.49 lm) with high volume cascade impactors, and the concentration of 17 elements (Al, As, Ca, Cd, Co, Cu, Fe, K, Li, Mg, Mn, Na, Ni, Pb, Sr, V, Zn) was determined by inductively coupled plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…The dendrograms show that the particle size distribution is mainly bimodal, with one cluster corresponding to the finer fraction 1.1-4.7 µm and the other cluster to the coarse mode 4.7-10 µm, shown by dotted boxes. Similar bimodal distributions have been reported earlier (Karanasiou et al, 2007;Toscano et al, 2011). Our observations show a close relationship between the ultrafine particles (<1.1 µm) and the coarser fraction (>5.8 µm).…”
Section: Particle Size Distributionsupporting
confidence: 75%
See 1 more Smart Citation
“…The dendrograms show that the particle size distribution is mainly bimodal, with one cluster corresponding to the finer fraction 1.1-4.7 µm and the other cluster to the coarse mode 4.7-10 µm, shown by dotted boxes. Similar bimodal distributions have been reported earlier (Karanasiou et al, 2007;Toscano et al, 2011). Our observations show a close relationship between the ultrafine particles (<1.1 µm) and the coarser fraction (>5.8 µm).…”
Section: Particle Size Distributionsupporting
confidence: 75%
“…The coarser particles (aerodynamic diameter > 3 µm) are thought to be formed by high temperature combustion, crustal erosion and road dust resuspension. The finer fractions are believed to be principally emitted from anthropogenic sources including combustion, high-temperature industrial activities and automotive traffic (Dockery & Pope, 1994;Toscano, Moret, Gambaro, Barbante, & Capodaglio, 2011). Knowledge on the size of the particles and their relationship to metals is vital in understanding health hazards in the atmosphere and to develop efficient methods and technologies to tackle these problems.…”
mentioning
confidence: 99%
“…Si, Al, Fe and Ti are generally used as reference elements, being abundant in soils, even if other choices have been made in research works: for example, Sr or Ti (Dongarrà et al, 2007;Teixeira et al, 2009). In the cases analysed Fe appears to be a suitable choice for the reference element because its origin in the Venice area has been indicated as mainly crustal in other research works in PM 10 (Rampazzo et al, 2008a(Rampazzo et al, , 2008bMasiol et al, 2010), in PM 2.5 (Stortini et al, 2009), in PM 3 and in PM 10−3 (Toscano et al, 2011). The EF is the comparison of the ratios of atmospheric concentrations of elements to a reference element with the same ratios in geological material (Watson et al, 2002), and it could furnish information on elements likely to originate from anthropogenic sources (Lu et al, 2007).…”
Section: Source Apportionment Methods Applied and Their Implementationmentioning
confidence: 99%
“…In particular, V has, also in this case, the highest EF in SA. Vanadium is emitted from all sources using heavy fuel oils such as ship engines and power plants (Becagli et al, 2012;Moreno et al, 2010;Toscano et al, 2011): therefore, this result is probably due to the input of air from the sea, as SA is relatively close to an important harbour and to a great coal power station localised in Savona city (Liguria region). To evaluate this hypothesis we calculated back-trajectories Taking wind direction and atmospheric conditions data into account and running deposition simulations by NOAA Hysplit Dispersion Model (Draxler and Rolph, 2015) and found that, particularly during summer days, air masses arriving in SA originate mainly from sea.…”
Section: Pm10 Concentration and Chemical Compositionmentioning
confidence: 99%